Functional plasticity of the human humerus. Issue 4 (26th February 2013) - Ibáñez‐Gimeno, Pere; De Esteban‐Trivigno, Soledad; Jordana, Xavier; Manyosa, Joan; Malgosa, Assumpció; Galtés, Ignasi
ABSTRACT The relationship between the mechanical loading undergone by a bone and its form has been widely assumed as a premise in studies aiming to reconstruct behavioral patterns from skeletal remains. Nevertheless, this relationship is complex due to the existence of many factors affecting bone structure and form, and further research combining structural and shape characteristics is needed. Using two‐block PLS, which is a test to analyze the covariance between two sets of variables, we aim to investigate the relationship between upper‐limb entheseal changes, cross‐sectional properties, and contour shape of the humeral diaphysis. Our results show that individuals with strongly marked entheseal changes have increased diaphyseal rigidities. Bending rigidities are mainly related to entheseal changes of muscles that cross the shoulder. Moreover, the entheseal changes of muscles that participate in the rotation of the arm are related to mediolaterally flatter and ventrodorsally broader humeral shapes in the mid‐proximal diaphysis. In turn, this diaphyseal shape is related to diaphyseal rigidity, especially to bending loadings. The shape of the diaphysis of the rest of the humerus does not covary either with rigidity or with entheseal changes. The results indicate that large muscular scars, such as those found in the mid‐proximal diaphyses, seem to be related to diaphyseal shape, whereas this relationship is not seen for areas with less direct influences of powerful muscles. Am J Phys Anthropol 150:609–617, 2013. © 2013 Wiley Periodicals, Inc.